KONTRIBUSI MATERI AKHLAK TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH - Abdullah Abdullah; Ahmad Noor Bayu Ramadani; Ririn Cahyani; Nisa Mutmainnah; Muhammad Rifqi Shahada Pratama (EMBRIO PENDIDIKAN: JURNAL PENDIDIKAN DASAR, 2026)
Character education is an urgent need in the midst of the moral crisis affecting the younger generation. Akidah Akhlak learning has a strategic position because it directly shapes students' faith and morals. This study aims to analyze the strengthening of character education through moral elements in Akidah Akhlak learning. The research uses a qualitative approach with a library research method. Data sources were obtained from searches in Google Scholar, DOAJ, and Portal Garuda databases (2015-2026) with relevant keywords. The results show that moral elements in Akidah Akhlak learning include four dimensions: (1) morals toward Allah (faith, piety, gratitude, trust); (2) morals toward oneself (maintaining health, controlling desires, avoiding heart diseases); (3) morals toward others (honesty, tolerance, helping, respect); (4) morals toward the environment (maintaining cleanliness, preserving nature). Character strengthening through these four dimensions is carried out through teacher role modeling, habituation of good behavior, value reflection, and integration in learning. The novelty of this article lies in the systematic mapping of the four moral elements and their relationship with the three pillars of character education (moral knowing, moral feeling, moral action). Practical implications suggest that Akidah Akhlak teachers need to internalize the four moral dimensions in an integrated manner in learning.